Corporate Social Performance (CSP) influences on Islamic Bank's financial performance / Amirul Afif Muhamat, Mohamad Nizam Jaafar, Mohd Faizal Basri - Muhamat, Amirul Afif; Jaafar, Mohamad Nizam; Basri, Mohd Faizal (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
This paper aims to assess the influence of corporate social performance (CSP) categories which are legal, ethical, economic and discretionary responsibilities over the Dummy Islamic Bank’s (the original name of the bank is remained confidential) financial performance. There are four components of CSP and findings indicate that this Islamic bank has fulfilled each category at minimum level - highest contribution was allocated for discretionary responsibility which is the pinnacle stage of CSP. This study has some limitations which need to be highlighted for future study. First, it only focused on one Islamic bank and may not reflect other Islamic banks in the country or in other region. Next, the period of observation is not lengthy to facilitate for more robust and rigorous analysis.